Electromagnetic study of surface enhanced Raman scattering of plasmonic-biomolecule: An interaction between nanodimer and single biomolecule. (April 2017) - Pandey, Gyanendra Krishna; Pathak, Nilesh Kumar; Uma, R.; Sharma, R.P.
Abstract: In this article we have investigated the electromagnetic surface enhanced Raman scattering (SERS) of single biomolecule adsorbed at the surface of spherical nanodimer. The SERS mechanism has been studied using first principle approach for spherical nanodimer geometry. The coupling of plasmonic concept to biomolecule results the broadband tunable enhancement in Raman gain factor. In this observation the enhancement factor was observed around ≈ 10 15 . The plasmonic properties of metal nanodimer are analysed in terms of surface plasmon resonances, extinction efficiency and polarisability that have been derived under quasistatic approximation. In this paper, various facets like interdipole separation, molecule distance and size of the plasmonic nanogeometry are taken into account to analyse the Raman gain factor. We also observe that the frequency range expands sufficiently which increases the broad detectability range of the molecule which generates signal even in the outside of Raman range i.e. in between IR to UV region. Lastly, the extinction spectra and electric field profile have been evaluated at resonance wavelength 364 nm. The comparison between electrostatic approach and numerical approach (using DDA) has also been done in terms of extinction spectra. Highlights: Investigation of SERS of single biomolecule in presence of sphere nanodimer. Raman enhancement factor=10 15 . Electrostatic and Numerical approach has been used to study SERS mechanism.